Lielupes kreisā krasta pieteku mazo HES ietekme uz vidi - Labanovska, Alvīne (Latvijas Universitāte, 2013)
Bakalaura darba par tēmu „Lielupes kreisā krastu pieteku mazo HES ietekme uz vidi” mērķis ir noskaidrot Lielupes kreisā krasta pieteku mazo HES ietekmi uz vidi. Pētījuma laikā no 2012. gada 14.-15. septembrim un no 2013. gada 5. -6. maijam ir apsekotas 11 mazās HES uz 5 upēm, kā arī to posmi aiz lejasbjefa, apmēram1 km attālumā aiz HES. Rezultāti liecina, ka mazo HES ietekmē upju vides stāvoklis pasliktinās. Vienlaicīgi negatīvu ietekmi rada arī difūzs un lokāla mēroga piesārņojums. Bakalaura darba apjoms ir 76 lappuses, tās papildina 31 attēls, 3 tabulas un 5 pielikumi. Atslēgas vārdi: mazās HES, ietekme uz vidi, Lielupes pietekas, upes ūdens kvalitāte, biogēnie elementi.

The aim of the Bachelor’s paper “Environmental Influence of the Small Hydroelectric Power Stations in the Left Bank Tributaries of the River Lielupe” is to determine the environmental impact of the small hydroelectric power stations in the left bank tributaries of the River Lielupe. During field research on 14-15 September 2012 and 5-6 May 2013 in total 11 small hydroelectric power stations in five rivers, as well as their afterbays after approximately 1 km from the hydroelectric power stations were inspected.Results of the study show that the small hydroelectric power stations contribute to the deterioration of river environment. Also diffuse and local pollution has negative impact. This Bachelor’s paper consists of 76 pages; it includes 31 images, 3 tables and 5 appendices. Keywords: small hydroelectric power stations, environmental influence of small hydroelectric power stations, tributaries of the River Lielupe, river water quality, biogenic elements
Environmental influence of the small hydroelectric power stations in the left Bank tributaries of the river Lielupe
Keywords: Vides zinātne